2020
DOI: 10.1187/cbe.19-06-0112
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Quality of Team Discussion: Discourse Analysis in an Undergraduate Team-Based Learning Biology Course

Abstract: Group activities as part of active-learning pedagogies are thought to be effective in promoting student learning in part because of the quality of discussion they engender in student teams. Not much is known, however, about which instructional factors are most important in achieving productive conversation or how these factors may differ among different collaborative pedagogies. We explored what provokes meaningful group discussions in a university physiology course taught using team-based learning (TBL). We w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…We accomplish this goal by providing a brief reflection on the learning experiences of faculty in these fields, connecting their learning process to their changes in teaching practices. active area of research in biology education (Perez et al, 2010;Smith et al, 2011;Leupen et al, 2020). Classroom discourse is important for two primary reasons.…”
Section: Introductionmentioning
confidence: 99%
“…We accomplish this goal by providing a brief reflection on the learning experiences of faculty in these fields, connecting their learning process to their changes in teaching practices. active area of research in biology education (Perez et al, 2010;Smith et al, 2011;Leupen et al, 2020). Classroom discourse is important for two primary reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In a typical TBL environment, teams sit around the tables with screens that make the content visible regardless of where they sit. Finally, this negative experience in team discussions could be because we (instructors) did not promote students questioning one another and student accountability (Leupen et al, 2020).…”
Section: Discussion During Team Problem-solving Exercisesmentioning
confidence: 99%
“…Asking for volunteers to share their ideas with the class will likely not affect the motivation of most students. However, studies suggest that randomly choosing students to share their thoughts with the class may motivate students to participate in the think and pair and enhance the quality of the pair discussion (Dallimore et al, 2013;Broeckelman-Post et al, 2016;Knight et al, 2016;Leupen et al, 2020). Some students have reported that random call motivates them to prepare for the share, because if they do not perform well, they may be judged by other students (Downing et al, 2020).…”
Section: Assumptions About the Sharementioning
confidence: 99%